A high efficiency three‐dimensional finite‐element electromagnetic radiation simulation tool. Issue 10 (14th July 2021) - Liu, Bingqi; Xu, Li; Wang, Hao; Yang, Siyi; Liu, Hangxin; Huang, Shucheng; Li, Bin
Abstract: In this article, a high efficiency three‐dimensional electromagnetic radiation simulation tool based on finite element method (FEM) is presented. This simulation tool has the functions of human‐computer interaction, constructing model, generating mesh, setting simulation parameters and making FEM analysis. In this simulation tool, the FEM analysis is the most critical part, so we mainly focus on the FEM electromagnetic radiation analysis technique in this article. In order to improve the efficiency of FEM analysis of electromagnetic radiation problems, we introduce the high order hierarchical vector basis function and the p‐type multiplicative Schwarz (p‐MUS) preconditioner to accelerate the iterative solution. What is more, we further improve the direct factorization process of p‐MUS preconditioner by multifrontal block incomplete Cholesky preconditioner. Numerical examples are presented to demonstrate the accuracy and efficiency of the proposed tool.